Unveiling the Neuromorphological Space - Costa, Luciano d.; Zawadzki, Krissia; Miazaki, Mauro; Viana, Matheus P.; Taraskin, Sergei (Frontiers in Computational Neuroscience, 2010)
This article proposes the concept of neuromorphological space as the multidimensional space defined by a set of measurements of the morphology of a representative set of almost 6000 biological neurons available from the Neuromorpho database. For the first time, we analyse such a large database in order to find the general distribution of the geometrical features. We resort to McGhee's biological shape space concept in order to formalise our analysis, allowing for comparison between the geometrically possible tree-like shapes, obtained by using a simple reference model, and real neuronal shapes. Two optimal types of projections, namely, principal component analysis and canonical analysis, are used in order to visualize the originally 20-D neuron distribution into 2-D morphological spaces. These projections allow the most important features to be identified. A data density analysis is also performed in the original 20-D feature space in order to corroborate the clustering structure. Several interesting results are reported, including the fact that real neurons occupy only a small region within the geometrically-possible space and that two principal variables are enough to account for about half of the overall data variability. Most of the measurements have been found to be important in representing the morphological variability of the real neurons.